(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The current research is aimed at developing liquid self-nanoemulsifying drug delivery system (liquid-SNEDDS) of Manidipine for enhanced solubility and oral bioavailability. The Manidipine SNEDDS are formulated with excipients comprising of Capmul MCM (oil phase), Transcutol P (surfactant) Lutrol L 300 as co-surfactant. The prepared fifteen formulations of Manidipine SNEDDS analysed for emulsification time, percentage transmittance, particle size, in vitro drug release, and stability studies. In vivo pharmacokinetic studies of the optimized formulation were carried out in Wistar rats in comparison with control (pure drug). The morphology of Manidipine SNEDDS indicates spherical shape with uniform particle distribution. The percentage drug release from optimized formulation F14 is 98.24 ± 5.14%. The particle size F14 formulation was 22.4 nm and Z-Average 23.3 nm. The PDI and zeta potential of Manidipine SNEDDS optimized formulation (F14) were 0.313 and-5.1mV respectively. From in vivo bioavailability data the optimized formulation exhibited a significantly greater Cmax and Tmax of the SNEDDS was found to be 3.42 ± 0.46ng/ml & 2.00 ± 0.05 h respectively. AUC0-∞ infinity for formulation was significantly higher (11.25 ± 3.45 ng.h/ml) than pure drug (7.45 ± 2.24ng. h/ml). Hence a potential SNEDDS formulation of Manidipine developed with enhanced solubility and bioavailability.